Impact of field dodder (Cuscuta campestris Yunk.) on physiological and anatomical changes in untreated and herbicide-treated alfalfa plants - Sarić-Krsmanović, Marija M; Božić, Dragana; Radivojević, Ljiljana; Gajić Umiljendić, Jelena; Vrbničanin, Sava (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
The effects of field dodder on physiological processes and the anatomy of alfalfa plants were examined under controlled conditions. The experiment included the following variants: N - noninfested alfalfa plants (control); I - infested alfalfa plants (untreated); T - infested plants treated with imazethapyr. Imazethapyr application rate was 100 g a.i. ha-1. The following parameters were checked: physiological - pigment content (chlorophyll a, chlorophyll b, total carotenoids); anatomical - stem parameters: thickness of epidermis and cortex, and diameter of stem and central cylinder; leaf parameters: thickness of epidermis, parenchyma and spongy tissue, mesophyll and underside leaf epidermis, and diameter of bundle sheath cells in alfalfa plants. Pigment contents and anatomical parameters were measured: prior to herbicide treatment (0 assessment), then 7 (I assessment), 14 (II assessment), 21 (III assessment), 28 (IV assessment) and 35 (V assessment) days after application (DAA).Field dodder was found to affect the contents of chlorophyll a, chlorophyll a and carotenoids in untreated alfalfa plants, causing significant reductions in pigment content.Conversely, percent reduction in the treated plants decreased 22-5% for chlorophyll a, 25-1%, for chlorophyll b, and 21-11% for carotenoids, while a stimulating effect of 1-6% was observed for the contents of chlorophyll b and carotenoids 35 DAA. Plants infested (untreated) by field dodder had lower values of most anatomical parameters, compared to noninfested plants. The measured anatomical parameters of alfalfa stems and leaves had significantly higher values in noninfested plants and plants treated with imazethapyr than in untreated plants.
Keywords: Field dodder; Alfalfa; Herbicide; Pigments; Anatomical parameters